دراسة طبيعة واتجاه العلاقة بين الاستثمار العام والاستثمار الخاص في سورية - اسماعيل, عصام (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يعتبر الاستثمار السبيل الأساسي لتحقيق النمو الاقتصادي، إلا أنه وعلى الرغم من ذلك نجد أن هنالك من يفرق بين الدور الذي يلعبه الاستثمار العام ونظيره من القطاع الخاص، فالبعض ينادي لتحييد الدولة عن فكرة المشاركة في العملية الاستثمارية، بينما يعتبر البعض الآخر أن الاستثمار العام شريك ضروري للاستثمار الخاص بل ومشجع له، ومن هنا تناقش هذه الدراسة أثر الاستثمار العام على الاستثمار الخاص في سورية، حيث توصلت إلى وجود علاقة قوية وسببية من الاستثمار العام باتجاه الاستثمار الخاص، كما توصلت إلى أن هذه العلاقة تكاملية على المدى الطويل بين هذين المتغيرين، بينما كان هناك أثر مزاحمة أو منافسة على المدى القصير بين كل من الاستثمار العام والاستثمار الخاص، وتتناول هذه الدراسة حالة الجمهورية العربية السورية خلال الفترة (1980- 2010). Investment is the key to economic growth. However, there are those who distinguish between the roles played by public investment and the private sector. Some advocate neutralizing the idea of ​​participation of government in the investment process, while others consider public investment as a necessary partner. The study discusses the impact of public investment on private investment in Syria, it reached a strong and causal relationship of public investment towards private investment, and concludes that thereis complementary relationship in the long term between these two variables, while there was the effect of crowding or competition in the short term between both public and private investment, and this study deals with the situation of the Syrian Arab Republic during the period 1980-2010.